Effects of Chromolaena Odorata Compost on Soil and Nutrient Uptake of Lettuce (Lactuca sativa) - Alima Maolidea Suri; Prapto Yudono (Universitas Muhammadiyah Yogyakarta, 2020)
The use of synthetic inorganic fertilizers containing chemical compounds cause soil quality to decrease. Chromolaena odorata are potential weeds used as a source of organic matter, which can be used as compost. This research aimed to determine the effect of Chromolaena odorata compost on the soil and nutrient uptake of lettuce. The research was conducted using a single factor experimental method arranged in a Randomized Complete Block Design. The treatments tested were the applications of C. odorata weed compost at various doses (222 grams/pot, 444 grams/pot, and 666 grams/pot) with control treatments of 200 ml/pot NPK Phonska (15:15:15), 320 grams/pot cow manure, and without fertilization. The experiment consisted of three blocks with three samples and three units of sample plants within each treatment. The results showed that the application of C. odorata weed compost significantly improved nutrition and nutrient uptake of lettuce. The dose of 444 grams/pot C. odorata weed compost was the best dose to increase soil quality and nutrient uptake of lettuce.